Efektivitas Penggunaan Intervensi Berbasis Internet Terhadap Gangguan Mental Pada Mahasiswa: Literatur Review - Atik Mardiani Kholilah; Tuti Nuraeni (Jurnal Keperawatan, 2019)
Depression is mental health problem which have high prevalence rate. Students be a spescial group which can be depression because many of stressor faced by them, but seldom students access mental health service. It’s because stigmatisasion, argue experience service and no available mental health service. Intervention based internet in mental disturbed can be need. This study purpose to describe implementation for health disturbed based web especially depression disturbed for students to increase community mental health. This study use litterature review methode. Database used Ebsco, PROQUEST, and Science Direct with keywords. Implementation and intervention for mental disturbed for students based web evidenced effective and effisient. Improvement intervention service based web can research for the effort to look for solution another chronic illness.